Vinča Burials in the Research of Miloje M. Vasić - Aleksandar Palavestra (University of Belgrade, 2021)
Miloje M. Vasić (1869–1956) is considered to be the founding father of Serbian archaeology. This paper directly challenges, as based on detailed archival research, the prevailing view that his excavation of the Vinča archaeological site is a model standard for Serbian archaeology. Instead, Vasić’s handling of the excavation was selective, non-systematic and destructive when viewed today from the perspective of modern practices.